Uzasadnienie decyzji jako akt etyczny - Kaczmarek, Przemysław (Er(r)go. Teoria - Literatura - Kultura, 2008)
Taking one of F. Kafka’s stories as a departure point the article revolves around the philosophical contexts of the ethical dilemma of decision making